PENTINGNYA PENDEKATAN KUALITATIF DALAM PENELITIAN DAN KONTRIBUSINYA BAGI PENDIDIKAN ISLAM - Nugroho, Arya Ficky; Sri Murhayati (STAI Nurul Falah Airmolek, 2024)
This research is motivated by the numerous phenomena related to behavior, habits, mindsets, and natural events that often occur without clear explanations. These phenomena, both social and natural, raise various questions and issues that require clarification. Qualitative research emerges as an approach aimed at understanding social reality from the perspective of the subjects being studied, allowing researchers to see the world as it is. This paper aims to examine the definitions, characteristics, objectives, and benefits of qualitative research, as well as its contributions to Islamic education. The method used in this research is library research, which involves gathering data from various scholarly literatures. The results of this research indicate that in the context of Islamic education, qualitative research helps develop a deep understanding of educational processes, culture, methods, and practices relevant to Islamic values. Qualitative research enables the development of new theories that can be used to improve Islamic educational practices, tailor educational approaches to specific needs and contexts, and provide innovative solutions to challenges faced in this field. Qualitative research significantly contributes to Islamic education in several ways. First, it allows for a deeper understanding of the experiences, perceptions, and practices of students and educators in the Islamic context. Second, it helps identify and develop more effective teaching methods that are relevant to Islamic values. Third, it supports the development of contextual and adaptive curricula that meet the needs of Muslim communities. Fourth, this research encourages critical reflection and continuous improvement in educational practices through a deep understanding of the social and cultural dynamics that influence Islamic education. Thus, the qualitative approach plays an essential role in enriching and strengthening the practices and theories of Islamic education, in line with the demands of the times and local contexts.